Chinese international students’ conceptualizations of wellbeing: A prototype analysis - Huang, Lanxi; Kern, Margaret L.; Oades, Lindsay G. (Frontiers in Psychology, 2022)
Wellbeing can mean different things to different people, even in the same culture with the same language. People living at the intersection of two languages and cultures, such as Chinese students studying in an English-speaking nation, not only speak a different language than their host country, but also may have different conceptualizations of wellbeing itself. This study investigated Chinese international students’ (aged 18-39, N=123) conceptualizations of wellbeing using a modified prototype analysis, which provides insights on people’s underlying structure of a construct as revealed through language. Chinese international students’ concepts of wellbeing were prototypically structured; key components of wellbeing included positive relationships, security, positivity/optimism, physical health, and self-strength. The findings broaden the understanding of layperson wellbeing conceptualizations, provide insights into the wellbeing related concepts and language that are most used by international Chinese students, and inform strategies that higher education institutions might adopt to effectively support Chinese international students’ wellbeing.